Innate Lymphoid Cells as Regulators of Epithelial Integrity: Therapeutic Implications for Inflammatory Bowel Diseases - Schulz-Kuhnt, Anja; Neurath, Markus F.; Wirtz, Stefan; Atreya, Imke (Frontiers in Medicine, 2021)
The occurrence of epithelial defects in the gut relevantly contributes to the pathogenesis of inflammatory bowel diseases (IBD), whereby the impairment of intestinal epithelial barrier integrity seems to represent a primary trigger as well as a disease amplifying consequence of the chronic inflammatory process. Besides epithelial cell intrinsic factors, accumulated and overwhelmingly activated proinflammatory immune cells and their secretome have been identified as critical modulators of the pathologically altered intestinal epithelial cell function in IBD. In this context, over the last ten years increasing levels of attention have been paid to the group of innate lymphoid cells (ILCs). This is in particular due to a preferential location of these rather newly described innate immune cells in close proximity to mucosal barriers, their profound capacity to secrete effector cytokines and their numerical and functional alteration under chronic inflammatory conditions. Aiming on a comprehensive and updated summary of our current understanding of the bidirectional mucosal crosstalk between ILCs and intestinal epithelial cells (IECs), this review article will in particular focus on the potential capacity of gut infiltrating type-1, type-2 and type-3 helper ILCs (ILC1s, ILC2s and ILC3s, respectively) to impact on the survival, differentiation and barrier function of IECs. Based on data acquired in IBD patients or in experimental models of colitis, we will discuss whether the different ILC subgroups could serve as potential therapeutic targets for maintenance of epithelial integrity and/or mucosal healing in IBD.